The Role of LAZ DASI NTB in Improving the Welfare of the People - Latifah, Cahya Aini; Mukhlisin, Mukhlisin; Ariani, Zaenafi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
One way to help alleviate poverty according to Islamic law is to grow zakat, so researchers are interested in researching the role of LAZ DASI NTB in improving the welfare of the people of Mataram City, to find out the role of LAZ DASI NTB in improving the welfare of the people of Mataram City, this study uses a qualitative research method, As for the results of this research, LAZ DASI NTB has carried out and worked on its role well, by carrying out various programs, namely: Active Role, LAZ DASI NTB assists with livable houses, water, and drilled wells. In the participatory role, LAZ DASI NTB collaborates with the city government, the passive role, LAZ DASI NTB conducts socialization. So, from the above role it has a positive influence where the welfare of the people of Mataram City increases with poverty decreasing.